A nexus of lipid and O-Glcnac metabolism in physiology and disease - Lockridge, Amber; Hanover, John A. (Frontiers in Endocrinology, 2022)
Although traditionally considered a glucose metabolism-associated modification, the O-linked β-N-Acetylglucosamine (O-GlcNAc) regulatory system interacts extensively with lipids and is required to maintain lipid homeostasis. The enzymes of O-GlcNAc cycling have molecular properties consistent with those expected of broad-spectrum environmental sensors. By direct protein-protein interactions and catalytic modification, O-GlcNAc cycling enzymes may provide both acute and long-term adaptation to stress and other environmental stimuli such as nutrient availability. Depending on the cell type, hyperlipidemia potentiates or depresses O-GlcNAc levels, sometimes biphasically, through a diversity of unique mechanisms that target UDP-GlcNAc synthesis and the availability, activity and substrate selectivity of the glycosylation enzymes, O-GlcNAc Transferase (OGT) and O-GlcNAcase (OGA). At the same time, OGT activity in multiple tissues has been implicated in the homeostatic regulation of systemic lipid uptake, storage and release. Hyperlipidemic patterns of O-GlcNAcylation in these cells are consistent with both transient physiological adaptation and feedback uninhibited obesogenic and metabolic dysregulation. In this review, we summarize the numerous interconnections between lipid and O-GlcNAc metabolism. These links provide insights into how the O-GlcNAc regulatory system may contribute to lipid-associated diseases including obesity and metabolic syndrome.